2012
DOI: 10.3109/10641963.2012.689044
|View full text |Cite
|
Sign up to set email alerts
|

Change in High-Sensitive Cardiac Troponin T on Hypertensive Treatment

Abstract: The aim of this study was to compare the differences in the levels of a highly sensitive cardiac troponin T (Hs-cTnT) between Losartan (LOS) plus hydrochlorothiazide (HCTZ) and amlodipine. Seventy-eight hypertensive patients were randomized to receive LOS/HCTZ or amlodipine for 8 weeks. Both treatments decreased clinic and 24-hour blood pressure to the same extent. The Hs-cTnT level was significantly reduced in the amlodipine group (P < .05), but such a reduction was not found in the LOS/HCTZ group in the uppe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
2
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 24 publications
0
7
2
1
Order By: Relevance
“…In present study, hs-cTnT was associated with age, hypertension, creatinine level, EF and hs-CRP level as well as diabetes and SYNTAX score in bivariate analysis. Previous studies reported the association between hs-cTnT with these parameters [22][23][24][25]. However, in our study, these relationships were not independent in multivariate regression analysis.…”
Section: Discussioncontrasting
confidence: 88%
“…In present study, hs-cTnT was associated with age, hypertension, creatinine level, EF and hs-CRP level as well as diabetes and SYNTAX score in bivariate analysis. Previous studies reported the association between hs-cTnT with these parameters [22][23][24][25]. However, in our study, these relationships were not independent in multivariate regression analysis.…”
Section: Discussioncontrasting
confidence: 88%
“…We cannot exclude the possibility that the reduction in TnT seen in this study is not linked to heart rate reduction, but to lowering of blood pressure. In a study by Hoshide et al, lowering of Tn concentration was seen after antihypertensive treatment with amlodipine . In the present patient population, the mean blood pressure was 141/91 mm Hg, and all the tested drug regimens reduced resting values of both systolic and diastolic blood pressure compared with baseline (Table ).…”
Section: Discussionmentioning
confidence: 48%
“… 19 21 In clinical studies, however, relationships among blood glucose concentrations, blood pressure levels, and blood concentrations of cardiac troponin were controversial. 22 25 Wallace et al 22 reported that diabetes mellitus was independently associated with cTnT elevation in the general population. However, Everett et al 23 reported that no significant relationship was observed between hemoglobin A 1c levels and hs-cTnT in nondiabetic subjects.…”
Section: Discussionmentioning
confidence: 99%